EXCHANGE RATE RISK AND PROFITABILITY OF EXPORT-ORIENTED INDIAN SMES - Harshita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Small and Medium Enterprises (SMEs) are the most significant part of the industrial economy in India and the largest exporters. However, fluctuations in the exchange rate expose export-oriented SMEs to foreign exchange risk, which directly affects profitability. In this paper, the association between exchange rate risk and the profitability of Indian SMEs has been looked into in terms of their hedging behaviour, their perception of risk, and the instruments they used to reduce losses. Based on primary and secondary data collected among SMEs in export-based industries like textiles, engineering and agro-based products, the research indicates that there are a greater number of firms with high turnover that are vigorous in using currency derivatives compared to smaller firms that use natural hedging or are not hedged at all. The results affirm the existence of a strong correlation between the exchange rate volatility, hedging strategy adopted, and profitability. It also develops recommendations to enhance risk management measures, raise awareness, and enhance the resilience of SMEs in international trade.